Habilidades para la vida Aproximaciones conceptuales - Parra Espitia, Laura Stella (Universidad Católica Luis Amigó, 2021)
In 1993, the World Health Organization proposed a psychosocial development approach called life skills; Its objective was to prevent and intervene in problems related to drug use, crime, and risky sexual behaviors, among others. Since then, programs based on this approach have been implemented to address various risk situations. The book "Skills for life. Conceptual Approaches " presents updated theoretical contributions of life skills, including cognitive, emotional, and social skills, with a perspective aimed at promoting mental health and human growth. The theoretical contributions presented can help psychosocial professionals such as psychologists, pedagogues, family therapists, and other actors who work with people at psychosocial risk. They also constitute a conceptual basis for the Life Skills approach.